Workeres, Documentary Photography and Authorship - Queiroga, Eduardo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2015)
This article discusses the tensions in the relationship between authorship and documentary photography. If on one hand the photography carries a number of possibilities of interpretation, this opening hinders the fundamental intent of the documentary photographer to report a phenomenon, to keep that bond with the referent. Several authorial strategies are undertaken to control dispersion, but it is also targeted to the extent that greater appearance of photographer may cause the deletion of the photographed. The author is a concept historically constructed and should be seen in its complexity, taking different nuances when the field is the photography. Will articulate the debate from the theoretical contributions of Michel Foucault, Antoine Compagnon, John Berger and Susan Sontag, articulating with the work of Sebastião Salgado, especially his book “Workers”.